2018
DOI: 10.1038/s41598-017-19031-0
|View full text |Cite
|
Sign up to set email alerts
|

19F-perfluorocarbon-labeled human peripheral blood mononuclear cells can be detected in vivo using clinical MRI parameters in a therapeutic cell setting

Abstract: A 19Fluorine (19F) perfluorocarbon cell labeling agent, when employed with an appropriate cellular MRI protocol, allows for in vivo cell tracking. 19F cellular MRI can be used to non-invasively assess the location and persistence of cell-based cancer vaccines and other cell-based therapies. This study was designed to determine the feasibility of labeling and tracking peripheral blood mononuclear cells (PBMC), a heterogeneous cell population. Under GMP-compliant conditions human PBMC were labeled with a 19F-bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
40
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 49 publications
2
40
0
Order By: Relevance
“…This excess of nanoparticles could limit further agent uptake. Nevertheless, labeling using 17 mg/ml of PLGA-NPs led to the incorporation of 5.5 ± 1.8 × 10 14 of F-19 per islet (approximately 5.5 ± 1.8 × 10 11 of F-19 nuclei), a finding that accords with published data (range of 10 11 –10 13 ) [ 35 37 ]. The nanoparticles have been previously shown to locate intracellularly in different cell types [ 16 , 17 ].…”
Section: Discussionsupporting
confidence: 89%
“…This excess of nanoparticles could limit further agent uptake. Nevertheless, labeling using 17 mg/ml of PLGA-NPs led to the incorporation of 5.5 ± 1.8 × 10 14 of F-19 per islet (approximately 5.5 ± 1.8 × 10 11 of F-19 nuclei), a finding that accords with published data (range of 10 11 –10 13 ) [ 35 37 ]. The nanoparticles have been previously shown to locate intracellularly in different cell types [ 16 , 17 ].…”
Section: Discussionsupporting
confidence: 89%
“…Vaccines prepared from PBMCs are FDA-approved for prostate cancer treatment [ 60 ]. Fink et al [ 61 ] investigated the use of PFC agents to label human PBMC samples from patients to enable in vivo detection (Table 1 ). The authors showed that all PBMC cells label, but to varying degrees, and uptake measurements in sorted cell subtypes yielded a labeling ( 19 F/cell) profile.…”
Section: Introductionmentioning
confidence: 99%
“…The limits of detection using 19 F-based imaging ranges from ~ 10 3 to ~ 10 5 cells per voxel [ 76 ]. For a given experiment, results depend on specific details, such as the PFC molecule and nanoemulsion used, the cell type (i.e., cell cytoplasm size) labeled, viability of cell culture and commensurate label uptake, image acquisition methods, magnetic field strength, and MRI detector configuration [ 40 , 46 , 61 , 72 ]. Looking forward, there are multiple, clinically-feasible, technical avenues for improving cell detection sensitivity that are vigorously being investigated involving new probe design and data acquisition methods [ 30 , 77 , 78 ].…”
Section: Introductionmentioning
confidence: 99%
“…Fluorine-19 MRI methods have shown promise for the detection of cell therapy products post-transfer, 12,[14][15][16]18,19,38 inflammatory infiltrates, [39][40][41][42][43] and molecular targets 44 in vivo in preclinical models. Moreover, first-generation 19 F probes based on PFC nanoemulsions have been used in a pilot clinical trial.…”
Section: Discussionmentioning
confidence: 99%
“…12,13 Fluorine-19-based MRI nanoemulsion probes are an option for non-invasively imaging of cell populations. [14][15][16][17][18][19][20] The 19 F nuclei have high intrinsic sensitivity, with 89% relative sensitivity compared to 1 H. De minimis endogenous 19 F in the body ensures that any MRI signals collected are from the introduced tracer probe. F-dense perfluorocarbon (PFC) molecules are often used to form nanoemulsion imaging probes that can be endocytosed by cells.…”
Section: Introductionmentioning
confidence: 99%